Eco-pharmacology: awareness and practice of drug disposal among medical students - Narasimhaiah, Manjunath G.; James, Aathira; Kalaburgi, Riyaj A. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Drugs are procured by the consumers from different sources. But most of the time it is in excess of the requirement, or not consumed completely. These unused drugs are disposed in a wrong manner which can lead to harmful effects on the environment. This study was to check the knowledge and practice by medical students. Methods: It was cross sectional observational study involving different batches of medical students by giving a semi-structured questionnaire. Results: A total of 165 participants (72 males, 93 females) from different batches of MBBS, predominantly 1st and 2nd year. Majority of them are aware of the term eco-pharmacology 70 (91%) and environmental effects 86 (06%). The most common mode of procurement is with prescription and possesses more than 50% of the expired drugs. Throwing back into the dustbin was the mode of disposal. Conclusions: There is poor knowledge of drug disposal behaviour. Sufficient training should be given to the medical students to protect the ecosystem.